From play to problem solving to Common Core: The development of fluid reasoning. Issue 3 (3rd July 2017) - Prince, Pauline
ABSTRACT: How and when does fluid reasoning develop and what does it look like at different ages, from a neurodevelopmental and functional perspective? The goal of this article is to discuss the development of fluid reasoning from a practical perspective of our children's lives: from play to problem solving to Common Core Curriculum. A review of relevant and current literature supports a connection between movement, including movement through free play, and the development of novel problem solving. As our children grow and develop, motor routines can become cognitive routines and can be evidenced not only in games, such as chess, but also in the acquisition and demonstration of academic skills. Finally, this article describes the connection between novel problem solving and the demands of the Common Core Curriculum.